A rare earth doped zirconium titanium cobalt hydrogen storage material and a preparation method thereof
Patent Information
- Application Number
- CN202510352545.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-03-24
AI Technical Summary
Existing ZrCo alloys suffer from problems such as harsh activation conditions, easy disproportionation reaction, reduced hydrogen storage capacity, and insufficient cycle stability in practical applications, making it difficult to balance disproportionation resistance and hydrogen storage performance.
By using rare earth element-doped Zr0.8Ti0.2Co alloys and controlling the grain boundaries and second phase, more hydrogen atom transport channels are formed, the microstructure and electronic structure are optimized, and the hydrogen absorption and desorption kinetics are improved.
Rare earth element-doped zirconium-titanium-cobalt hydrogen storage materials significantly improve hydrogen absorption rate and hydrogen storage capacity, shorten activation cycle, and enhance the alloy's cycle stability and anti-disproportionation performance.
Smart Images

Figure CN120400650B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen storage materials technology, and in particular to a rare earth-doped zirconium-titanium-cobalt hydrogen storage material and its preparation method. Background Technology
[0002] With the continued rise in demand for renewable resources, hydrogen energy, as a renewable energy source with enormous potential, is widely used in aerospace, battery manufacturing, hydrogen power generation, and electric vehicles. ZrCo alloys, due to their potential hydrogen storage capacity, are widely used in the storage, supply, and recovery of hydrogen isotopes and are considered a potential alternative to uranium. Compared to uranium, ZrCo alloys are non-radioactive, non-flammable, and have strong helium-binding capabilities. Their hydrogen absorption capacity is approximately 1.9 wt%, and the pressure of the hydrogen absorption platform is approximately 10... -3 However, ZrCo still faces certain challenges in practical applications. First, the activation conditions for ZrCo alloys are quite demanding, making activation difficult. Second, ZrCo alloys are prone to disproportionation reactions under repeated hydrogen absorption / desorption cycles or high-temperature environments, producing a non-hydrogen-absorbing ZrCO2 phase and a difficult-to-desorb ZrH2 phase. This reduces hydrogen storage capacity, thus limiting its further development and application. Simultaneously, the cycling stability and anti-poisoning properties of ZrCo alloys also need further improvement.
[0003] In recent years, to overcome the above-mentioned difficulties, research has focused on element doping, surface improvement, and preparation process optimization. Among the many methods, element doping is particularly prevalent. ZrCo alloy, as a typical AB-type hydrogen storage material, often relies on doping with different elements for performance optimization. At the A end, substitute elements such as Ti, Hf, and Nb are widely used; while at the B end, substitute elements include Ni, Fe, Mn, Cu, and Mo. According to existing research data, when Ti is doped into ZrCo alloy, the high-temperature disproportionation resistance is significantly improved, but the hydrogen absorption kinetics decrease. When Hf is doped into ZrCo alloy, the disproportionation resistance is improved, but Hf is expensive. When Nb is doped into ZrCo alloy to replace Zr, the initial activation performance is improved, but the maximum hydrogen absorption capacity decreases (Journal of Alloys and Compounds 784(2019)1062-1070). The disproportionation resistance after Fe and Ni replace Co is controversial. Al substitution for Co enhances cycle stability, but reduces hydrogen uptake capacity from 1.91 wt% to 1.67 wt%. Mo substitution for Co shortens the initial activation time, with hydrogen uptake decreasing from 1.89 wt%. to 1.66 wt%. Pd substitution for Co improves cycle stability, but reduces maximum hydrogen uptake, and Pd is relatively expensive. Based on the above analysis, elemental substitution is an important means to improve the hydrogen storage isotopes of ZrCo. A-terminal elemental substitution significantly improves the thermodynamic properties of ZrCo, while B-terminal substitution is more important for improving the kinetic properties of ZrCo alloys. However, currently reported methods all have certain limitations. There is an urgent need to find a solution that can improve both disproportionation resistance and hydrogen storage kinetics in alloy hydrogen storage materials. Summary of the Invention
[0004] The purpose of this invention is to provide a rare earth-doped zirconium-titanium-cobalt hydrogen storage material and its preparation method, so as to solve the problem that the above-mentioned ZrCo alloy material cannot simultaneously achieve anti-disproportionation performance and hydrogen storage performance.
[0005] To achieve the above objectives, the first aspect of this invention provides a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material, the general chemical formula of which is: Zr 0.8 Ti 0.2-x M x Co, where x is 0 to 0.05, and M is a rare earth element with an atomic radius greater than Ti.
[0006] Zr 0.8 Ti 0.2Co alloy ingots exhibit excellent anti-disproportionation properties when the Ti content reaches 20 mol% of Zr and total Ti content. In particular, after a disproportionation treatment lasting up to 10 hours, the hydrogen pressure of the alloy remains almost unchanged, demonstrating significant stability. However, the hydrogen absorption rate is poor, therefore, in existing technologies, Zr... 0.8 Ti 0.2 While Co alloys exhibit excellent resistance to disproportionation, their hydrogen absorption kinetics are unsatisfactory, and rare-earth element-doped ZrCo-based alloys have not been reported. Based on the characteristics of rare-earth elements, this invention aims to explore the potential enhancement effects of adding elements such as Y and Ce on the hydrogen storage capacity of ZrTiCo alloys, in order to provide new ideas and directions for the research and application of hydrogen storage materials. This invention focuses on Zr... 0.8 Ti 0.2 Doping Co alloys with rare earth elements induces more hydrogen atom transport channels through grain boundaries and second-phase regulation, which is beneficial to improving the hydrogen atom diffusion rate. This invention's rare earth element doping can lower the hydrogen atom adsorption energy and dehydrogenation energy barrier, improving hydrogen adsorption and desorption kinetics. Simultaneously, rare earth elements can increase the adsorption sites for hydrogen atoms, further enhancing hydrogen storage capacity. Furthermore, rare earth elements can optimize the microstructure of hydrogen storage alloys and regulate electronic structure, thereby optimizing kinetic performance.
[0007] Preferably, x is 0.01 to 0.05.
[0008] Preferably, M is at least one of Y and Ce.
[0009] When M is Y, the atomic radius of Y is larger than that of Ti. As the content of Y increases, the lattice constant and unit cell volume also increase, providing more effective hydrogen storage sites and thus improving hydrogen storage capacity. Y atoms readily create grain boundary precipitation effects in the microstructure, providing more diffusion channels for hydrogen atoms and improving hydrogen absorption kinetics.
[0010] When M is Ce, the atomic radius of Ce is larger than that of Ti. Even a small amount of Ce substituting for Ti increases the lattice constant and cell volume, providing more effective hydrogen storage sites and thus improving hydrogen storage capacity. Ce substitution helps form a network-distributed second phase, which facilitates faster dissociation and diffusion of hydrogen molecules, enhancing hydrogen absorption kinetics. However, excessive Ce substitution of Ti leads to the formation of a CeCo2 impurity phase, reducing hydrogen absorption and cycle stability.
[0011] In summary, appropriate rare earth element substitution can improve the maximum hydrogen absorption capacity, hydrogen absorption kinetics, and cycle stability of ZrTiCo hydrogen storage alloys.
[0012] A second aspect of this invention provides a method for preparing rare-earth-doped zirconium-titanium-cobalt hydrogen storage materials, comprising the following steps:
[0013] (1) Metal raw materials with a purity greater than 99.9% are processed according to Zr 0.8 Ti 0.2-x M x Co is added to the stoichiometric ratio in the smelting furnace for smelting;
[0014] (2) The ingot obtained after smelting is crushed and ground to obtain alloy powder;
[0015] (3) The alloy powder is tightly wrapped with a nickel mesh and then placed in a stainless steel container for vacuum treatment;
[0016] (4) After vacuum treatment, the alloy powder is placed in hydrogen gas for activation treatment until the alloy powder reaches the hydrogen absorption saturation state, thus obtaining zirconium-titanium-cobalt hydrogen storage material.
[0017] Preferably, in step (1), the smelting process is as follows: smelting is carried out in a water-cooled copper furnace using an electric arc smelting furnace under a helium atmosphere.
[0018] Preferably, in step (1), in order to ensure uniform distribution of metal elements, the smelted ingot is flipped and remelted more than three times.
[0019] Preferably, in step (2), the particle size of the alloy powder is 200-300 mesh.
[0020] Preferably, in step (2), the crushing is done by manual crushing, and the grinding is done by combining coarse grinding with stainless steel mortar and fine grinding with agate mortar.
[0021] Preferably, in step (2), after the obtained alloy ingot is surface treated, it is polished with a fine grinding wheel to remove the oxide film, and then cut into small pieces with pliers for easy subsequent processing.
[0022] Preferably, in step (2), conductive thermal embedding material is used to embed these small pieces at a temperature of about 130°C to enhance their stability and operability for further experimental analysis.
[0023] Preferably, in step (3), the temperature of vacuum treatment is 180-220°C and the time is 1-3 hours.
[0024] The purpose of vacuum treatment in this invention is to remove various gaseous impurities adhering to the alloy surface.
[0025] Preferably, in step (4), the activation treatment temperature is 200-300℃, the time is 0.5-2h, and the hydrogen pressure is 1-5MPa.
[0026] Preferably, in step (4), in order to ensure the purity of the zirconium-titanium-cobalt hydrogen storage material and prevent oxidation, the prepared zirconium-titanium-cobalt hydrogen storage material is stored in a glass bottle containing anhydrous ethanol.
[0027] Therefore, the present invention employs the above-mentioned rare-earth-doped zirconium-titanium-cobalt hydrogen storage material and its preparation method, which has the following beneficial effects:
[0028] (1) This invention combines formulation optimization and microstructure improvement, using rare earth element M and transition metals Zr, Ti and Co for alloying, which reduces the activation conditions of ZrCo alloy, shortens the activation cycle, improves its microstructure, overcomes the problem of poor hydrogen absorption kinetics of ZrCo-based hydrogen storage alloy, and makes its advantages apparent, significantly improving the hydrogen absorption and desorption performance of the alloy.
[0029] (2) Zr prepared by the present invention 0.8 Ti 0.2-x M x Co hydrogen storage materials are easy to activate, have high hydrogen storage capacity, and good hydrogen absorption and desorption performance.
[0030] (3) The atomic radii of the rare earth elements Y and Ce in this invention are larger than those of Ti. The rare earth elements replace the titanium element, and the cell parameters are increased, which is beneficial to increasing the number of hydrogen storage sites and thus improving the maximum hydrogen storage capacity of the ZrTiCo alloy.
[0031] (4) The addition of rare earth elements in this invention accelerates the hydrogen absorption kinetics of the alloy. Rare earth element Y forms grain boundary precipitation, providing more effective pathways for hydrogen atom diffusion. The oxide phase of rare earth element Ce forms a network structure, which has a catalytic effect on the dissociation and diffusion of hydrogen atoms. The hydrogen diffusion is very active, which significantly shortens the incubation period. The rapid activation of the alloy and the catalytic effect of the new phase also significantly improve the hydrogen absorption performance and hydrogen absorption rate of the alloy. This provides strong support for the optimization of the kinetic performance of ZrTiCo alloy in the prior art.
[0032] (5) In the process of crushing and grinding, the present invention adopts a combination of manual crushing, coarse grinding with stainless steel mortar and fine grinding with agate mortar to form a large number of crystal defects, increase the nucleation points and diffusion channels of hydrogen, further reduce the thermal stability of hydrides and improve the hydrogen absorption and desorption kinetics of alloys.
[0033] (6) The hydrogen storage alloy preparation method provided by the present invention has readily available raw materials, common equipment, relatively mild process conditions, simple operation, short preparation time, and is suitable for large-scale manufacturing and widespread promotion.
[0034] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0035] Figure 1 XRD patterns of hydrogen storage materials in Comparative Example 1 and Examples 1-3;
[0036] Figure 2 SEM images of the hydrogen storage materials in Comparative Example 1 and Example 2;
[0037] Figure 3 EDS diagram of the hydrogen storage material in Example 2;
[0038] Figure 4 XRD patterns of hydrogen storage materials in Comparative Example 1 and Examples 4-6;
[0039] Figure 5 SEM images of the hydrogen storage materials in Examples 4-6;
[0040] Figure 6 EDS diagram of the hydrogen storage material in Example 4;
[0041] Figure 7 The initial activation kinetics curves are for the hydrogen storage materials in Comparative Example 1 and Examples 1-3;
[0042] Figure 8 The initial activation kinetics curves are for the hydrogen storage materials in Comparative Example 1 and Examples 4-6;
[0043] Figure 9 XRD patterns of the corresponding hydrides of the hydrogen storage materials in Comparative Example 1 and Examples 1-3;
[0044] Figure 10 XRD patterns of the corresponding hydrides of the hydrogen storage materials in Comparative Example 1 and Examples 4-6;
[0045] Figure 11 Cyclic stability curves of hydrogen storage materials in Comparative Example 1 and Examples 1-3;
[0046] Figure 12 Cyclic stability curves of hydrogen storage materials in Comparative Example 1 and Examples 4-6;
[0047] Figure 13 The images show the XRD patterns of the hydrogen storage materials in Comparative Example 1 and Examples 1-3 after 10 cycles of hydrogen absorption and desorption.
[0048] Figure 14 The images show the XRD patterns of the hydrogen storage materials in Comparative Example 1 and Examples 4-6 after 10 cycles of hydrogen absorption and desorption. Detailed Implementation
[0049] The present invention will be further described below. It should be noted that this embodiment is based on the present technical solution and provides detailed implementation methods and specific operation processes, but the present invention is not limited to this embodiment.
[0050] Comparative Example 1
[0051] A Zr 0.8 Ti 0.2 The preparation method of Co hydrogen storage material includes the following steps:
[0052] (1) High-purity metal raw materials (Zr, Ti, Co) with a purity of over 99.9% are accurately weighed according to the molar ratio Zr∶Ti∶Co=0.8∶0.20∶1, and then electric arc melting is carried out in a water-cooled copper crucible to ensure that an alloy ingot with uniformly mixed metal raw materials is obtained.
[0053] To further ensure a uniform distribution of components in the alloy ingot, the ingot was flipped at least six times during the smelting process to ensure a more consistent mixing effect.
[0054] After surface treatment, the obtained alloy ingots were polished with a fine grinding wheel to remove the oxide film, and then further cut into small pieces using pliers. A portion of the alloy samples were selected for subsequent mounting processing for further experimental analysis; while another portion was successively coarsely ground in a stainless steel mortar and finely ground in an agate mortar, ultimately obtaining alloy powder with a particle size range of 200–300 mesh, providing necessary sample preparation for subsequent performance testing and characterization. This step helps enhance the surface quality of the alloy and provides suitable samples for subsequent experiments.
[0055] (2) The alloy powder is tightly wrapped with a nickel mesh, then placed in a stainless steel container and subjected to a vacuum treatment at 200°C for 2 hours to remove various gaseous impurities adhering to the alloy surface.
[0056] (3) After vacuum treatment, the alloy powder is activated for 1 hour under hydrogen pressure at 250°C to ensure that it reaches the hydrogen absorption saturation state.
[0057] Example 1
[0058] The difference between this embodiment and Comparative Example 1 is that the chemical formula of the hydrogen storage material is different. The chemical formula of the hydrogen storage material in this embodiment is Zr. 0.8 Ti 0.2-x Y x Co, x = 0.01, the preparation and testing methods of the hydrogen storage material are the same as those of Comparative Example 1.
[0059] Example 2
[0060] The difference between this embodiment and Comparative Example 1 is that the chemical formula of the hydrogen storage material is different. The chemical formula of the hydrogen storage material in this embodiment is Zr. 0.8 Ti 0.2-x Y xCo, x = 0.03, the preparation method and testing process of the hydrogen storage material are the same as those of Comparative Example 1.
[0061] Example 3
[0062] The difference between this embodiment and Comparative Example 1 is that the chemical formula of the hydrogen storage material is different. The chemical formula of the hydrogen storage material in this embodiment is Zr. 0.8 Ti 0.2-x Y x Co, x = 0.05, the preparation method and testing process of the hydrogen storage material are the same as those of Comparative Example 1.
[0063] Example 4
[0064] The difference between this embodiment and Comparative Example 1 is that the chemical formula of the hydrogen storage material is different. The chemical formula of the hydrogen storage material in this embodiment is Zr. 0.8 Ti 0.2-x Ce x Co, x = 0.01, the preparation method and testing process of the hydrogen storage material are the same as those of Comparative Example 1.
[0065] Example 5
[0066] The difference between this embodiment and Comparative Example 1 is that the chemical formula of the hydrogen storage material is different. The chemical formula of the hydrogen storage material in this embodiment is Zr. 0.8 Ti 0.2-x Ce x Co, x = 0.03, the preparation method and testing process of the hydrogen storage material are the same as those of Comparative Example 1.
[0067] Example 6
[0068] The difference between this embodiment and Comparative Example 1 is that the chemical formula of the hydrogen storage material is different. The chemical formula of the hydrogen storage material in this embodiment is Zr. 0.8 Ti 0.2-x Ce x Co, x = 0.05, the preparation method and testing process of the hydrogen storage material are the same as those of Comparative Example 1.
[0069] Test case
[0070] (1) The alloy hydrogen storage materials prepared in the examples and comparative examples were characterized by XRD, SEM and EDS.
[0071] Figure 1The XRD patterns of the hydrogen storage materials in Comparative Example 1 and Examples 1-3 are shown in the figures. It can be seen that the hydrogen storage material prepared in Comparative Example 1 has a cubic ZrCo main phase structure, with no other second phase observed. The hydrogen storage material prepared in Example 1 also has a cubic ZrCo main phase structure, with no other second phase observed, and its phase composition is basically consistent with that of the hydrogen storage material in Comparative Example 1. The refinement results are shown in Table 1. The cell parameters of Example 1 are slightly larger than those of Comparative Example 1, and the atomic radius of Y is larger than that of Ti. After Y partially replaces Ti, the cell volume increases. The structure of the hydrogen storage material prepared in Example 2 is... The cubic ZrCo main phase, with no other second phase observed, is basically consistent with the phase of the hydrogen storage material in Comparative Example 1. The refinement results are shown in Table 1. The cell parameters of Example 2 are slightly larger than those of Example 1, proving that the cell volume increases with the increase of Y atom doping. The hydrogen storage material prepared in Example 3 has a cubic ZrCo main phase, with no other second phase observed, and is basically consistent with the phase of the hydrogen storage material in Comparative Example 1. The refinement results are shown in Table 1. The cell parameters of Example 3 are slightly larger than those of Example 2, proving that the cell volume increases with the increase of Y atom doping.
[0072] Table 1. List of cell parameters of hydrogen storage materials in the examples and comparative examples.
[0073]
[0074]
[0075] Figure 2 SEM images of the hydrogen storage materials prepared in Comparative Example 1 and Example 2, from... Figure 2 As can be seen from the SEM image of the hydrogen storage material in Comparative Example 1, it shows a single main phase with no obvious second phase, which is consistent with the XRD results. The SEM image of the hydrogen storage material in Example 2 shows that after rare earth element doping with Ti, a certain grain boundary precipitation phenomenon occurs.
[0076] Figure 3 The image shows the EDS diagram of the hydrogen storage material prepared in Example 2. Figure 3 As can be seen, the precipitates at the grain boundaries are mainly Y elements. Since the atomic radius of Y is relatively large, it exceeds the maximum solid solubility of the main phase, thus resulting in grain boundary segregation.
[0077] Figure 4 The XRD patterns of the hydrogen storage materials prepared in Comparative Examples 1 and Examples 4-6 are shown below. Figure 4As can be seen from the table, the hydrogen storage materials prepared in Examples 4 to 6 all have a cubic ZrCo main phase structure, and a CeO2 second phase was also observed. This is because Ce is prone to oxygen absorption and oxidation during the melting process. The results of the refinement are shown in Table 1. Compared with Comparative Example 1, the cell parameters of the hydrogen storage materials in Examples 4 to 6 are slightly increased. The atomic radius of Ce is larger than that of Ti. After Ce partially replaces Ti, the cell volume increases.
[0078] Figure 5 The images shown are SEM images of the hydrogen storage materials prepared in Examples 4-6. Figure 5 Images (a), (b), and (c) show the hydrogen storage materials prepared in Examples 4, 5, and 6, respectively. Figure 5 As can be seen, the hydrogen storage material of Example 4 contains a tiny white phase precipitation, consistent with the CeO2 second phase corresponding to XRD; the hydrogen storage material of Example 5 contains a tiny white phase precipitation, the white phase intertwined into a network structure, consistent with the CeO2 second phase corresponding to XRD. The network second phase structure can provide diffusion transport channels for hydrogen atoms, which helps to improve the hydrogen absorption kinetics; the hydrogen storage material of Example 6 contains a white phase intertwined into a network structure, consistent with the CeO2 second phase corresponding to XRD, and at the same time, an uneven dark phase appears, which is the CeCo2 phase.
[0079] Figure 6 The EDS diagram for Example 4 is shown below. Figure 6 As can be seen, the grain boundary precipitates are mainly CeO2. Since Ce atoms have a large atomic radius, exceeding the maximum solid solubility of the main phase, grain boundary segregation occurs.
[0080] (2) The hydrogen absorption and desorption performance of the alloy hydrogen storage materials prepared in the examples and comparative examples were tested.
[0081] To accurately evaluate the alloy's performance in hydrogen absorption / desorption cycles, the alloy samples were subjected to hydrogen absorption treatment under preset temperature and hydrogen pressure conditions. Subsequently, these alloy samples were placed in a dynamic vacuum environment for dehydrogenation. During the hydrogen absorption phase, the temperature was controlled at 250°C and the hydrogen pressure at 2 MPa (the specific hydrogen pressure was determined according to experimental requirements). The dehydrogenation phase involved dynamic venting at 400°C. The above procedures were repeated during the hydrogen absorption / desorption cycle.
[0082] Figure 7 The initial activation kinetics curves of the hydrogen storage materials in Comparative Example 1 and Examples 1-3 are shown below. Figure 7As shown in Table 2, the hydrogen storage material of Comparative Example 1, under conditions of 2 MPa and 250°C, reached a maximum hydrogen absorption capacity of 1.708 wt%, and the time required to reach 90% of the maximum hydrogen absorption capacity was 2379 s. The hydrogen storage material of Example 1, under conditions of 2 MPa and 250°C, reached a maximum hydrogen absorption capacity of 1.852 wt%. The addition of rare earth elements increased the cell volume, providing more tetrahedral and octahedral active sites for hydrogen atom storage, thus increasing the hydrogen absorption capacity compared to Comparative Example 1. Example 1 reached 90% of the maximum hydrogen absorption capacity in 290 s, and the hydrogen absorption rate was approximately 7 times higher than that of Comparative Example 1. The addition of rare earth elements significantly improved the hydrogen absorption kinetics. Y doping significantly improved the hydrogen absorption rate and capacity of the alloy, shortening the incubation period for hydrogen absorption. The hydrogen storage material of Example 2, under conditions of 2 MPa and 250°C, reached a maximum hydrogen absorption capacity of 1.708 wt%, and the time required to reach 90% of the maximum hydrogen absorption capacity was 2379 s. a) Hydrogen absorption was performed at 250℃, reaching a maximum hydrogen absorption capacity of 1.935 wt%. The time required for Example 1 to reach 90% of the maximum hydrogen absorption capacity was 123 s, indicating a further improvement in the hydrogen absorption rate compared to Example 1. The addition of rare earth elements significantly improved the hydrogen absorption kinetics. The grain boundary effect constructed by Y doping can provide more diffusion paths for hydrogen atoms, significantly improving the hydrogen absorption rate and capacity of the alloy. The hydrogen storage material of Example 3 was subjected to hydrogen absorption at 2 MPa and 250℃, reaching a maximum hydrogen absorption capacity of 1.922 wt%, which is higher than that of Comparative Example 1. However, with further increases in Y element, the hydrogen absorption capacity decreased. Due to the limited solid solubility of the BCC main phase, the excess Y atoms exceeded the solid solubility limit, resulting in Y segregation. The segregated phase and the increased grain boundary effect reduced the hydrogen storage capacity. The hydrogen storage material in Example 3 reached 90% of its maximum hydrogen absorption capacity in 65 seconds, and the hydrogen absorption rate was further improved compared to Comparative Example 1. The hydrogen absorption kinetics were significantly improved after the addition of rare earth elements. The grain boundary effect constructed by Y doping can provide more diffusion paths for hydrogen atoms, significantly improving the hydrogen absorption rate and hydrogen absorption capacity of the alloy and shortening the hydrogen absorption incubation period.
[0083] Figure 8 The initial activity kinetic curves of the hydrogen storage materials prepared in Comparative Examples 1 and Examples 4-6 are shown below. Figure 8As shown in Table 2, the hydrogen storage material of Example 4, under conditions of 2 MPa and 250°C, achieved a maximum hydrogen absorption capacity of 1.913 wt%. The addition of the rare earth element Ce increased the cell volume, providing more tetrahedral and octahedral active sites for hydrogen atom storage, thus increasing the hydrogen absorption capacity compared to Comparative Example 1. Example 4 reached 90% of its maximum hydrogen absorption capacity in 190 s, with an absorption rate approximately 12 times higher than Comparative Example 1. The addition of rare earth element Ce significantly improved the hydrogen absorption kinetics, and Ce doping significantly enhanced the alloy's hydrogen absorption rate and capacity, shortening the incubation period. The hydrogen storage material of Example 5, under conditions of 2 MPa and 250°C, achieved a maximum hydrogen absorption capacity of 1.935 wt%. The addition of rare earth element Ce further improved the absorption capacity. The increased cell volume provides more tetrahedral and octahedral active sites for hydrogen atom storage, thus increasing the hydrogen absorption capacity compared to Comparative Example 1. Example 5 achieved a maximum hydrogen absorption capacity of 90% in 72 seconds, a further improvement over Example 4. The addition of rare earth element Ce significantly enhanced the hydrogen absorption kinetics. The network structure of the second phase provided more diffusion channels for hydrogen atoms. Simultaneously, rare earth Ce exhibits strong catalytic activity and a strong affinity for hydrogen atoms. Ce doping significantly improved the hydrogen absorption rate and capacity of the alloy, shortening the incubation period for hydrogen absorption. The hydrogen storage material in Example 6 achieved a maximum hydrogen absorption capacity of 1.785 wt% under conditions of 2 MPa and 250 °C. The maximum hydrogen storage capacity of Example 6 decreased compared to Example 5, possibly due to the non-hydrogen-absorbing CeCo2. In Example 6, the time required to reach the maximum hydrogen absorption capacity of 90% was 37 seconds, which is a further improvement compared to Example 5. The hydrogen absorption kinetics were significantly improved after the addition of rare earth element Ce. The network structure of the second phase provides more diffusion channels for hydrogen atoms. At the same time, rare earth Ce has a strong catalytic effect and a strong affinity for hydrogen atoms. The doping of Ce significantly improved the hydrogen absorption rate and hydrogen absorption capacity of the alloy and shortened the hydrogen absorption incubation period.
[0084] Table 2. Hydrogen storage performance test results for comparative and example cases.
[0085]
[0086]
[0087] After hydrogenation, the hydrogen storage materials of the examples and comparative examples were characterized by XRD. Figure 9 The XRD patterns of the corresponding hydrides of the hydrogen storage materials in Comparative Examples 1 and Examples 1-3 are shown below. Figure 9 As can be seen from the data, the hydrides of Comparative Example 1 and Examples 1-3 are all ZrCoH3 hydrides. Figure 10 The XRD patterns of the corresponding hydrides of the hydrogen storage materials in Comparative Examples 1 and Examples 4-6 are shown below. Figure 10 As can be seen from the examples, the hydrides in Examples 4 to 6 are all ZrCoH3 hydrides.
[0088] Hydrogen absorption and desorption cycle tests were conducted on the hydrogen storage materials of the comparative examples and embodiments. Figure 11 To present the hydrogen absorption and desorption cycle test results of the hydrogen storage materials in Comparative Examples 1 and Examples 1-3, from... Figure 11 As can be seen, after 10 cycles of hydrogen absorption and desorption, the hydrogen storage capacity retention rate of the hydrogen storage material in Comparative Example 1 was 87.77%; after 10 cycles of hydrogen absorption and desorption, the hydrogen storage capacity retention rates of the hydrogen storage materials in Examples 1 to 3 were 90.27%, 88.94%, and 88.23%, respectively. Figure 12 To compare the hydrogen absorption and desorption cycle test results of the hydrogen storage materials in Examples 1 and 4-6, from... Figure 12 As can be seen, after 10 cycles of hydrogen absorption and desorption, the hydrogen storage capacity retention rates of the hydrogen storage materials in Examples 4-6 were 92.43%, 92.44%, and 84.2%, respectively. The hydrogen storage capacity retention rate of Example 6 was slightly lower than that of Comparative Example 1, which may be due to the presence of the second phase CeCo2, which reduced the cycle stability of the alloy. Overall, the rare earth Y and Ce-doped ZrTiCo-based alloys achieved good results in improving hydrogen absorption capacity and hydrogen absorption kinetics.
[0089] The products from the comparative and example samples after hydrogen adsorption / desorption cycling tests were analyzed by XRD. Figure 13 The XRD patterns of the products after hydrogen adsorption / desorption cycling tests of Comparative Example 1 and Examples 1-3 are shown below. Figure 13 As can be seen, the main phase of the hydrogen storage material in Comparative Example 1 is still the BCC structure, exhibiting good structural stability; the main phase of the products in Examples 1 to 3 is also still the BCC structure, exhibiting good structural stability. This fully demonstrates that rare earth doping is an effective way to modify the hydrogen storage performance of ZrTiCo alloy, which can improve the maximum hydrogen absorption capacity and hydrogen absorption rate while ensuring good cycle stability. Figure 14 The XRD patterns of the products after hydrogen adsorption / desorption cycling tests of Comparative Examples 1 and Examples 4-6 are shown below. Figure 14 As can be seen, the main phase of the products in Examples 4 to 6 is still the BCC structure main phase, which also shows good structural stability.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A rare-earth-doped zirconium-titanium-cobalt hydrogen storage material, characterized in that: The general chemical formula for zirconium-titanium-cobalt hydrogen storage materials is Zr. 0.8 Ti 0.2-x M x Co, where x is 0.01~0.05, M is a rare earth element with an atomic radius greater than Ti, and M is Y or Ce; The main phase of the hydrogen storage material is a cubic ZrCo phase; when M is Y, Y elements precipitate at the grain boundaries; when M is Ce, a CeO2 second phase exists in the hydrogen storage material, and the CeO2 phase is distributed in a network when x≥0.
03.
2. The method for preparing a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 1, characterized in that: Includes the following steps: (1) Metal raw materials with a purity greater than 99.9% are processed according to Zr 0.8 Ti 0.2-x M x Co is added to the stoichiometric ratio in the smelting furnace for smelting; (2) The ingots obtained after smelting are crushed and ground by manual crushing, and then coarsely ground by stainless steel mortar and finely ground by agate mortar to obtain alloy powder with a particle size of 200~300 mesh. (3) The alloy powder is tightly wrapped with a nickel mesh and then placed in a stainless steel container for vacuum treatment; (4) After vacuum treatment, the alloy powder is placed in hydrogen gas for activation treatment until the alloy powder reaches the hydrogen absorption saturation state to obtain zirconium titanium cobalt hydrogen storage material.
3. The method for preparing a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 2, characterized in that: In step (1), the smelting process is as follows: in a helium atmosphere, the metal raw materials are placed in a water-cooled copper crucible for smelting using an electric arc smelting method.
4. The method for preparing a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 2, characterized in that: In step (1), the smelted ingot is flipped and remelted more than three times.
5. The method for preparing a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 2, characterized in that: In step (3), the vacuum treatment temperature is 180~220℃ and the time is 1~3h.
6. The method for preparing a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 2, characterized in that: In step (4), the activation treatment temperature is 200~300℃, the time is 0.5~2h, and the hydrogen pressure is 1~5MPa.
7. The method for preparing a rare-earth-doped zirconium-titanium-cobalt hydrogen storage material according to claim 2, characterized in that: In step (4), the prepared zirconium-titanium-cobalt hydrogen storage material is stored in a glass bottle containing anhydrous ethanol.
